Numerical simulation of high-temperature creep deformation in Zr-2.5%Nb pressure tubes of CANDU reactors - Corzo, Santiago Francisco (2020)
The present paper deals with the development of a numerical approach to predict thermal creep in pressure tubes of CANDU nuclear power reactors. This phenomenon plays a crucial role under accident conditions, where the core can reach high temperature and the pressure tubes can suffer thermal creep with important radial deformation usually named “Ballonning”. The Balloning strain in CANDU pressure tubes is a difficult issue from the mathematical point of view due to the visco-plastic nature of the deformation, and the material properties of the tubes, which are made of a Zr–2.5%Nb alloy that presents micro-structural phase change at temperatures close to 800∘C. For this reason, an explicit strategy was implemented in OpenFOAM-5.0® assuming the uniaxial deformation in radial direction, neglecting the rotational strains. The proposed model is assessed by reproducing experimental tests before to be applied to model the response of CANDU pressure tubes under Station Blackout and Loss Of Coolant Accident conditions.